(untitled) (Journal of Economic Research & Business Administration, 2016)
One of important economic characteristics of the bank activity received during the financial analysis is liquidity. Management of bank liquidity is rather difficult process, and such indicators as profitability, profit ability and, in general, the general financial condition of commercial bank in many respects depend on its quality. Liquidity is of great importance for all banks as its ability in due time depends on a condition of bank liquidity to register payments, to return funds from deposit accounts, to answer for other obligations. In domestic practice in the conditions of liquidity crisis the problem of low bank liquidity is especially actual. Low liquidity is a source of internal instability of a banking system, limiting possibilities of expansion of volume of financial operations of banks and doing a banking system unstable to external negative impacts.